Information Retrieval Behavior of Research Students: A Case of Higher Education Commission (HEC) Digital Library of Pakistan - Shafiq Ur Rehman1 , Murtaza Ashiq (IJoLIS, 2024)
Purpose: This study aimed to explore the perceptions of Pakistani research students regarding the Higher Education Commission (HEC) digital library‟s usage, problems, issues, and effectiveness of its federated search tool (Summon).